Protecting‐Group‐Free Solid‐Phase Anchoring of Polyphenolic C‐Glucosidic Ellagitannins and Synthesis of 1‐Alkylamino‐Vescalagin Derivatives (Eur. J. Org. Chem. 23/2014). Issue 23 (August 2014) - Douat, Céline; Berni, Emanuela; Jacquet, Rémi; Pouységu, Laurent; Deffieux, Denis; Quideau, Stéphane
Abstract : The cover picture shows a protecting‐group‐free approach for the chemo‐ and stereoselective amination of the C ‐glucosidic ellagitannin vescalagin. This bioactive plant polyphenol is a characteristic secondary metabolite of fagaceous woody species such as oak ( Quercus sp.). Its benzylic secondary alcohol group is first substituted by a thioether unit, which is then activated by the use of a sulfenyl chloride. The resulting thiosulfonium ion reacts with primary amines to afford β‐1‐alkylamino‐vescalagin derivatives. This article by S. Quideau et al. onp. 4963 ff describes this selective amination of such a structurally unique plant polyphenol by a protocol that was adapted to both solution‐ and solid‐phase synthesis conditions. The background picture shows an oak tree hundreds of years old, which is certainly packed with vescalagin, as the amount of this ellagitannin can reach up to 2 %percnt; by weight of dry heartwood.